2017
DOI: 10.1111/nph.14677
|View full text |Cite
|
Sign up to set email alerts
|

The nectar spur is not only a simple specialization for long‐proboscid pollinators

Abstract: Since the time of Darwin, biologists have considered the floral nectar spur to be an adaptation representing a high degree of plant specialization. Nevertheless, some researchers suggest that nature is more complex and that even morphologically specialized plants attract a wide spectrum of visitors. We observed visitors on Impatiens burtonii (Balsaminaceae) and measured the depth of the proboscis insertion into the spur, the distance of the nectar surface from the spur entrance and the visitor's effectiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…This new species to science is refereed as Melanostoma sp. in Vlašánková et al (2017). In the present study, the division between Bacchini sensu stricto and Melanostomini stated by Thompson & Skevington (2014) will be followed to discuss the results.…”
Section: Taxonomymentioning
confidence: 76%
See 1 more Smart Citation
“…This new species to science is refereed as Melanostoma sp. in Vlašánková et al (2017). In the present study, the division between Bacchini sensu stricto and Melanostomini stated by Thompson & Skevington (2014) will be followed to discuss the results.…”
Section: Taxonomymentioning
confidence: 76%
“…The new species of Melanostoma was collected during the field work done by Vlašánková et al (2017) in the Mendong Buo area (6.592699°N, 10.189999°E; 2100-2200 m above sea level), ca. 5 km south-east of Big Babanki, in the Bamenda Highlands, North-West Province, Cameroon.…”
Section: Taxonomymentioning
confidence: 99%
“…Geometric morphometric analyses can enrich studies on the phenotypic evolution of flowers and of their pollinators. In the case of the spurred flowers of Delphinieae, for which the pollinators are expected to be specialists (but see Hollens et al 2017;Vlašánková et al 2017), comparing the form of the dorsal floral module with the front of the pollinator's body would allow testing the mutual fit of both structures. The collections (herbarium, entomological and ornithological) kept at natural history museums would be very useful in this respect.…”
Section: First Step Towards Investigating the Evolution Of Delphinieamentioning
confidence: 99%
“…Several studies reported that selectivity of some hoverfly species depends on certain plant traits. Overall, hoverflies seem to visit mostly open bowl-shaped flowers (Branquart and Hemptinne, 2000), where they feed on both nectar and pollen (Gilbert, 1981), but some of them have relatively long proboscises which allow them to reach nectar even in flowers with relatively long spurs (Gilbert, 1981;Vlašánková et al, 2017). In addition, inflorescence height also affects flower visitation by some species (Gervasi and Schiestl, 2017;Klecka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%